Optogenetic inhibition of D1R containing nucleus accumbens neurons alters cocaine-mediated regulation of Tiam1 - Chandra, Ramesh; Lenz, Jeffrey D.; Gancarz, Amy M.; Chaudhury, Dipesh; Schroeder, Gabrielle L.; Han, Ming-Hu; Cheer, Joseph F.; Dietz, David M.; Lobo, Mary Kay (Frontiers in Molecular Neuroscience, 2013)
Exposure to psychostimulants results in structural and synaptic plasticity in striatal medium spiny neurons (MSNs). These cellular adaptations arise from alterations in genes that are highly implicated in the rearrangement of the actin cytoskeleton, such as Tiam1. Previous studies have demonstrated a crucial role for dopamine receptor 1 (D1)-containing striatal MSNs in mediating psychostimulant induced plasticity changes. These D1-MSNs in the nucleus accumbens (NAc) positively regulate drug seeking, reward, and locomotor behavioral effects as well as the morphological adaptations of psychostimulant drugs. Here, we demonstrate that rats that actively self-administer cocaine display reduced levels of Tiam1 in the NAc. To further examine the cell type specific contribution to these changes in Tiam1 we used optogenetics to selectively manipulate NAc D1-MSNs or dopamine receptor 2 (D2) expressing MSNs. We find that repeated ChR2 activation of D1-MSNs but not D2-MSNs caused a down-regulation of Tiam1 levels similar to the effects of cocaine. Further, activation of D2-MSNs, which caused a late blunted cocaine-mediated locomotor behavioral response, did not alter Tiam1 levels. We then examined the contribution of D1-MSNs to the cocaine-mediated decrease of Tiam1. Using the light activated chloride pump, eNpHR3.0, we selectively inhibited D1-MSNs during cocaine exposure, which resulted in a behavioral blockade of cocaine-induced locomotor sensitization. Moreover, inhibiting these NAc D1-MSNs during cocaine exposure reversed the down-regulation of Tiam1 gene expression and protein levels. These data demonstrate that altering activity in specific neural circuits with optogenetics can impact the underlying molecular substrates of psychostimulant mediated behavior and function.